Trajectory of depressive and anxious symptoms in patients with pre-existing diagnosis undergoing bariatric surgery: Systematic review and meta-analysis protocol: Depression and anxiety in bariatric surgery - G. Castro, Isadora; R. Afonso, João Pedro; A. Cunha, Regina Célia; M. S. Cunha, Bernardo; M. Pires, Luis Felipe; Oliveira, Jordão R.; Andrade, Lucas S.; Oliveira, Luís Vicente F.; Paixão, Heren N. C. (Manual Therapy, Posturology & Rehabilitation Journal, 2025)
Background: Severe obesity is a chronic and multifactorial condition associated with significant physical and psychological impacts, including high rates of depression and anxiety. Bariatric surgery is recognized as the most effective treatment for cases of severe obesity, promoting sustained weight loss, improvement of comorbidities, and enhancement of quality of life. However, the trajectory of psychological symptoms after the procedure is still uncertain, especially among patients who already experienced emotional distress before the surgery. Objective: This systematic review and meta-analysis protocol aims to synthesize evidence on the changes in depression and anxiety levels in adults with severe obesity and pre-existing symptoms undergoing bariatric surgery. Methods: Longitudinal cohort studies, either prospective or retrospective, that assess symptoms of depression and anxiety before and after surgery, using validated psychometric instruments such as the Beck Depression Inventory, Hospital Anxiety and Depression Scale, Beck Anxiety Inventory, and Generalized Anxiety Disorder-7, will be included. The search will be conducted in the PubMed, Web of Science, and Scopus databases, without language restrictions, starting from June 26, 2025. The methodological quality will be assessed using the Newcastle-Ottawa Scale, and the quantitative synthesis will be conducted thru a random-effects meta-analysis when there is homogeneity among the studies. Conclusion: It is expected that this review will provide consistent evidence on the evolution of depressive and anxious symptoms after bariatric surgery, contributing to the improvement of psychological follow-up strategies and strengthening the comprehensive care of patients with severe obesity.